Controlled Microfabrication of High‐Aspect‐Ratio Structures in Silicon at the Highest Etching Rates: The Role of H2O2 in the Anodic Dissolution of Silicon in Acidic Electrolytes. (12th December 2016) - Cozzi, Chiara; Polito, Giovanni; Kolasinski, Kurt W.; Barillaro, Giuseppe
Abstract : In this work the authors report on the controlled electrochemical etching of high‐aspect‐ratio (from 5 to 100) structures in silicon at the highest etching rates (from 3 to 10 µm min −1 ) at room temperature. This allows silicon microfabrication entering a previously unattainable region where etching of high‐aspect‐ratio structures (beyond 10) at high etching rate (over 3 µm min −1 ) was prohibited for both commercial and research technologies. Addition of an oxidant, namely H2 O2, to a standard aqueous hydrofluoric (HF) acid electrolyte is used to dramatically change the stoichiometry of the silicon dissolution process under anodic biasing without loss of etching control accuracy at the higher depths (up to 200 µm). The authors show that the presence of H2 O2 reduces the valence of the dissolution process to 1, thus rendering the electrochemical etching more effective, and catalyzes the etching rate by opening a more efficient path for silicon dissolution with respect to the well‐known Gerischer mechanism, thus increasing the etching speed at both shorter and higher depths. Abstract : In this work, Giuseppe Barillaro and co‐workers show that the addition of H2 O2 to a standard aqueous hydrofluoric (HF) acid electrolyte allows a dramatic change in the stoichiometry of the silicon dissolution process under anodic biasing to be achieved without loss of etching control accuracy at the higher depths. This enables the room temperature fabrication of high‐aspect‐ratio (from 10 to 100) microstructures in silicon at etching rates (from 3 to 10 µm min −1 ) that were previously unattainable.